Reconstruction of Thiospinel to Active Sites and Spin Channels for Water Oxidation. Issue 2 (5th December 2022) - Wu, Tianze; Sun, Yuanmiao; Ren, Xiao; Wang, Jiarui; Song, Jiajia; Pan, Yangdan; Mu, Yongbiao; Zhang, Jianshuo; Cheng, Qiuzhen; Xian, Guoyu; Xi, Shibo; Shen, Chengmin; et al.
Abstract: Water electrolysis is a promising technique for carbon neutral hydrogen production. A great challenge remains at developing robust and low‐cost anode catalysts. Many pre‐catalysts are found to undergo surface reconstruction to give high intrinsic activity in the oxygen evolution reaction (OER). The reconstructed oxyhydroxides on the surface are active species and most of them outperform directly synthesized oxyhydroxides. The reason for the high intrinsic activity remains to be explored. Here, a study is reported to showcase the unique reconstruction behaviors of a pre‐catalyst, thiospinel CoFe2 S4, and its reconstruction chemistry for a high OER activity. The reconstruction of CoFe2 S4 gives a mixture with both Fe–S component and active oxyhydroxide (Co(Fe)O x H y ) because Co is more inclined to reconstruct as oxyhydroxide, while the Fe is more stable in Fe–S component in a major form of Fe3 S4 . The interface spin channel is demonstrated in the reconstructed CoFe2 S4, which optimizes the energetics of OER steps on Co(Fe)O x H y species and facilitates the spin sensitive electron transfer to reduce the kinetic barrier of O–O coupling. The advantage is also demonstrated in a membrane electrode assembly (MEA) electrolyzer. This work introduces the feasibility of engineering the reconstruction chemistry of the precatalyst for high performance and durable MEA electrolyzers. Abstract : The electrochemical reconstruction of thiospinel CoFe2 S4 evolves both oxyhydroxide species as active site and Fe3 S4 component as spin channel, which is unique. The reconstructed CoFe2 S4 shows state‐of‐art oxygen evolution reaction activity because of a strong magnetic anisotropy at the interface between oxyhydroxide and Fe3 S4 components. The reconstructed configuration also benefits a robust performance in membrane electrolyzers.